PENGARUH PENAMBAHAN KARAGENAN TERHADAP KUAT TARIK DAN BIODEGRADASI EDIBLE FILM DARI PATI KULIT SINGKONG - Christina Lydia Makmur; Indang Dewata; Alizar Alizar; Budhi Oktavia (Universitas Negeri Padang, 2021)
Edible film is a thin plastic with a thickness of less than 0.25 mm which serves to protect food products. This study aims to determine the effect of adding carrageenan to edible films made from cassava peel starch (Manihot utilissima) on the mechanical properties and biodegradation of edible films. This experimental study varied the addition of carrageenan with various concentrations of 0%, 0.5%, 1%, 1.5%, 2%. In this edible film, data obtained that the addition of carrageenan affects the tensile strength and biodegradation of the edible film. The maximum tensile strength was obtained by adding 18.54 MPa of carrageenan. Biodegradation of edible film is increasing along with the addition of carrageenan. The mechanical properties obtained in this study have met the standard of JIS Z1707 edible film.